Morphological and Crystallinity Studies of Nanofiber Cellulose Based on Sargassum sp. Using Multistep Preparation - Nurhayati, Nurhayati; Irianto, Hari Eko; Chalid, Mochamad; Riastuti, Rini (Universitas Gadjah Mada, 2025)
This study aims to investigate the crystallinity and morphological characteristics of cellulose nanofibers (CNF) isolated from Sargassum seaweed through a multistep preparation. The isolation was conducted in stages, including alkalinization, bleaching, and mechanical reduction in fiber size. In addition to observing the outcomes at each isolation stage, three mechanical processes were implemented to generate CNF. The observed parameters included fiber morphology analyzed using scanning electron microscopy (SEM) and fiber crystallinity tested using X-ray diffraction (XRD). The results indicated that Sargassum mostly exhibits a type Iα structure of cellulose. The multistep treatment, combined with mechanical processing, resulted in finer fibers and an improved crystallinity index, reaching a maximum value of 70.39%. These findings suggest that cellulose nanofibers from Sargassum have the potential to be used in sustainable biomedical materials.